Analisis dan Perancangan Sistem E-Marketing pada PT. Nordic Lift Truck - Haris Setia Budi; Wednes Pujiasmoro; Herjandi Wijaya; Yuliyanti Yuliyanti (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The purpose of research is to analyze the current marketing system at PT.Nordick Lift Truck in order to identify the existing problems faced by the company and to identify its weaknesses. Additionally, this research designs a web based Marketing system. The system has been designed to give facilitation for customer to get information abaut material of tutorial activity fast and efficient. The methodologies used are literature study, observation, interview, questionaire, analysis and design with 7-stages E-Marketing. It isconcluded that e-CRM system that has been designed supports information access easily and fast. The e-Marketing application consists of features such as Online Register, Contact us, Download, News, and Complaint. It is expected to help deliver and maintain customer satisfaction by building  a close relationship to the customers.